Optimal Incentives to Domestic Investment in the Presence of Capital Flight. (IMF Working Papers; Working Paper ;, 1989)
This paper develops a model of an open economy which employs distortionary taxes to finance public consumption, and with an access to the world capital market. The paper examines the efficiency of quantity restrictions on capital exports and the accompanying set of taxes. A distinction is made between a benchmark case where the government can fully tax foreign-source income and a more realistic case where the government cannot effectively tax foreign-source income.